2020
DOI: 10.3390/app10155258
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Dynamic Performance and Riding Comfort of a Straddle-Type Monorail Subjected to Moving Trains

Abstract: The driving comfort of a straddle-type monorail, while considering the influence of the bridge structure, was studied on the basis of multibody dynamics and the finite element method. In this study, the coupled vehicle-bridge model was established through SIMPACK and ANSYS; the 3D model of the bridge was established in ANSYS, and the vehicle model with 35 degrees of freedom (DOFs) was established in SIMPACK. The influence of the vehicle speed, pier height, track irregularity, and vehicle load on riding comfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…16 Τime-integration algorithms developed for the VBI problem may either solve the coupled system directly (coupled algorithms) (Yang et al, 2016), or solve the vehicle subsystem and bridge subsystem separately in a co-simulation environment (iterative algorithms). 3,17 An alternative approach that potentially incorporates the advantages of both coupled and iterative schemes is the dynamic localized version of the Lagrange multipliers method. This methodology introduces an additional artificial auxiliary point at the contact interface, assigns two sets of Lagrange multipliers, and states two sets of kinematic constraints between the extra point and the other contact points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Τime-integration algorithms developed for the VBI problem may either solve the coupled system directly (coupled algorithms) (Yang et al, 2016), or solve the vehicle subsystem and bridge subsystem separately in a co-simulation environment (iterative algorithms). 3,17 An alternative approach that potentially incorporates the advantages of both coupled and iterative schemes is the dynamic localized version of the Lagrange multipliers method. This methodology introduces an additional artificial auxiliary point at the contact interface, assigns two sets of Lagrange multipliers, and states two sets of kinematic constraints between the extra point and the other contact points.…”
Section: Introductionmentioning
confidence: 99%
“…These indicators of railway bridges were well-evaluated and formed a specific evaluation criterion and a serviceability limit state for the bridge system. 17 Riding safety consists of running safety and running stability. Running safety is related to the fact that the train will not derail or overturn, which is usually evaluated by the derailment coefficient, the rate of wheel load reduction, the lateral wheelset force, the overturning coefficient, and other indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al [10] used the idea of dynamic flexibility to establish a frequency-domain model of high-speed railway vehicle-track-bridge vertical coupling dynamics and solved the dynamic response of the track system and bridge structure under unit simple harmonic excitation and wheelrail geometric roughness excitation, respectively. Based on multibody dynamics and finite element methods, Gao et al [11] have developed a coupled vehicle-bridge model by SIMPACK and ANSYS. A 3D model of the bridge was built in ANSYS, and a vehicle model with 35 degrees of freedom was built in SIMPACK.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of the coupled vibration mechanism of railway bridges and trains, it is generally difficult for general-purpose finite element software to accurately consider the complex wheel-rail interaction relationship. In the finite element analysis of bridge structures, none of the literature [2][3][4][5][6][7][8][9][10][11][12][13] has considered the effect of mass-shear heterocentricity of the cross section. ere are even fewer studies on the coupled vibration analysis of the bridge considering the mass-shear heterocentre.…”
Section: Introductionmentioning
confidence: 99%
“…He et al established an improved trainbridge interaction model, investigated the dynamic performance of the suspended monorail vehicle on the circle curve bridge, and found that the rational allocation of shock absorbers could effectively suppress the vibration of the vehicle [14]. Gao et al established a coupled vehicle-bridge model of the straddle-type monorail based on multibody dynamics and the finite element method and studied the influences of vehicle speed, pier height, track irregularity, and vehicle load on ride comfort [15]. Taking the straddletype monorail as the research object, Junchao et al established a dynamic model of vehicles and the tire-track contact model to analyze the influences of different velocities and tire stiffness on vibration characteristics of vehicles [16].…”
Section: Introductionmentioning
confidence: 99%